Repercussions of Compromising Sacred Texts in Bapedi Culture: Reflections - (:unkn) unknown (My University, 2022)
In Bapedi society, discussions concerning the interpretation of sacred texts in African context with a focus on Indigenous Knowledge Systems in Africa have increased in frequency and intensity. Many of these discussions reflect sacred texts and African Traditional Religion, as well as theologizing in Africa. Among some Christians especially elderly people, ‘Exodus 20:5, 6; 34:6, 7; Numbers 14:18 & Deuteronomy 5:9,10’; generally speaking, are regarded as teaching sacred texts in Africa. This paper shares some insights highlighted by some Christians and elderly people during informal interviews. The purpose of this study is to investigate the repercussions of compromising the sacred texts ‘Exodus 20:5, 6; 34:6, 7; Numbers 14:18 & Deuteronomy 5:9, 10’ with special reference to Bapedi people’s cultural context. The following research question is therefore considered to address the objective of this study: Why are innocent children and grandchildren suffering because of the deeds of their parents, but not their parents who are the focus of blame? The study employs historical research approach. Informal interviews, video and audio recordings were used to collect data. The results show that innocent children and grandchildren of the parents who have completely forgotten about their roots, and who are mesmerized by other theological beliefs are going through difficult times. It is concluded that undermining taboos, customs, beliefs, and practices, seems to be the primary factors in negatively influencing innocent children and grandchildren to go through difficult times in life and struggle to survive.
Keywords: African Research